Parallel power-converter operation for efficient wid power extraction - Ju, Xuesong (2019)
Wind energy was invented some time ago, but it did receive much dramatic improvement with power control system and was only drive with generators, and pass the pulsations in the wind to the grid. The main reason was a proper control system was not taking into consideration to regulate the varied frequency and voltage produced by wind turbine system. Wind power industry has been an unprecedented development with the development of wind power technology and the implementation of the policy encouragement. So, researching converter and control strategy and the application of power electronic devices are the two key factors to improving the wind quality. The aim of this project is to build a converter system to analyse the behaviours of wind turbine system. Its characteristics and working principle will be explained in this report. In addition, a model will be constructed using PSIM software to simulate the overall system.